Osteogenic differentiation of mesenchymal stem cells using hybrid nanofibers with different configurations and dimensionality. Issue 7 (17th May 2017) - Gugutkov, Dencho; Awaja, Firas; Belemezova, Kalina; Keremidarska, Milena; Krasteva, Natalia; Kyurkchiev, Stanimir; Gallego‐Ferrer, Gloria; Seker, Sukran; Elçin, Ayşe Eser; Elçin, Yaşar Murat; Altankov, George
Abstract: Novel, hybrid fibrinogen/polylactic acid (FBG/PLA) nanofibers with different configuration (random vs aligned) and dimensionality (2‐D vs 3‐D environment) were used to control the overall behavior and the osteogenic differentiation of human adipose‐derived mesenchymal stem cells (ADMSCs). Aligned nanofibers in both the 2‐D and 3‐D configurations are proved to be favored for osteodifferentiation. Morphologically, we found that on randomly configured nanofibers, the cells developed a stellate‐like morphology with multiple projections; however, time‐lapse analysis showed significantly diminished cell movements. Conversely, an elongated cell shape with advanced cell spreading and extended actin cytoskeleton accompanied with significantly increased cell mobility were observed when cells attached on aligned nanofibers. Moreover, a clear tendency for higher alkaline phosphatase activity was also found on aligned fibers when ADMSCs were switched to osteogenic induction medium. The strongest accumulation of Alizarin red (AR) and von Kossa stain at 21 days of culture in osteogenic medium were found on 3‐D aligned constructs while the rest showed lower and rather undistinguishable activity. Quantitative reverse transcription‐polymerase chain reaction analysis for Osteopontin (OSP) and RUNX 2 generally confirmed this trend showing favorable expression of osteogenic genes activity in 3‐D environment particularly in aligned configuration. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2065–2074, 2017.